1936
DOI: 10.1017/s0022172400043655
|View full text |Cite
|
Sign up to set email alerts
|

A Study Of English Diets By The Individual Method: Part II. Women

Abstract: SUMMARY1. The food intakes of sixty-three women of the English middle class have been studied by the individual method and compared with those of men which were described in a previous paper.2. The average calorie consumption was 2187 per day. Although it is not suggested that this is the optimum intake, it would appear from these results that the “man value” of a woman is 0·7, and not 0·8 as is usually supposed. The individual calorie consumptions varied from 1453 to 3110 per day.3. The average daily protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1938
1938
1998
1998

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…large differences in self-reported energy intake (EI) of subjects with apparently similar lifestyles and body weights (e.g. Widdowson, 1936;Widdowson & McCance, 1936;Edholm et al 1970). Taken at face value these dietary intake studies suggested that some people apparently consumed large amounts of energy but remained lean, while others appeared to consume only small-to-moderate amounts of food and gain weight easily.…”
Section: Recent Trends In Energy Balance Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…large differences in self-reported energy intake (EI) of subjects with apparently similar lifestyles and body weights (e.g. Widdowson, 1936;Widdowson & McCance, 1936;Edholm et al 1970). Taken at face value these dietary intake studies suggested that some people apparently consumed large amounts of energy but remained lean, while others appeared to consume only small-to-moderate amounts of food and gain weight easily.…”
Section: Recent Trends In Energy Balance Researchmentioning
confidence: 99%
“…(c) Very little evidence of adaptive thermogenesis was found in human subjects when the components of the energy equation (intake, expenditure and balance) were independently measured (Norgen & Durnin, 1980;Forbes et al 1986;Ravussin et al 1986). As James (1992) points out, studies that have supported the notion of luxuskonsumption (Widdowson, 1936;Widdowson & McCance, 1936;Miller et at. 1967;Sims, 1968;Sims et al , 1973Edholm et al 1970) have only inferred, not measured, the one unambiguously measurable outcome variable; that is, an increased rate of heat output from the body.…”
Section: Recent Trends In Energy Balance Researchmentioning
confidence: 99%
“…Frequency distribution of calorie intake of sixty-three men and sixty-three women (from Widdowson & McCance, 1936). The variations are evident at 1-2 years and probably begin earlier.…”
mentioning
confidence: 98%
“…This explanation is unlikely since the mean urinary pH of the sixty females above child-bearing age (over 45) included in this study, was higher (5 73) than the mean for all females (5*71). It seems more likely that the sex difference in urinary pH is due to the higher protein intake of men as compared with women (Widdowson and McCance, 1936), for it has long been known (Bernard, 1878;Hunt, 1956) that a high protein intake leads to the excretion of a more acid urine. The sex difference in urinary osmolality may also be related to differences in the protein intake of men and women.…”
Section: Discussionmentioning
confidence: 99%